The Outrageousness of Outrage: Daphne du Maurier’s ‘Monte Verità’ - Christine Reynier (Études Britanniques Contemporaines, 2013)
This article takes as its starting point the lack of critical interest in du Maurier’s short story ‘Monte Verità’. Informed by Margaret Forster’s biography and a paper by Zižek, it confronts the contradictory and ambivalent conceptions of outrage developed in the narrative and reads the short story as a reflection on the nature of outrage and as raising ethical questions connected with it, what is called here, in reference to Stuart Hall, the ethics of outrage. Those general reflections on outrage are finally shown to take on a more specific meaning when the context of the story and its connection with modernist aesthetics is taken into account.